Dynamic Rendezvous Based Routing Algorithm on Sparse Opportunistic Network Environment - Jiradett Kerdsri; Komwut Wipusitwarakun (International Journal of Distributed Sensor Networks)
An opportunistic network is a network where the nodes need to communicate with each other even if existing routes between them may not permanently exist due to the nodes’ random movement. Most routing algorithms employ a paradigm by which a node can keep the receiving messages, carrying the messages with them when moving and then forwarding the messages to the opportunistic meeting nodes when possible. This routing model works well in the networks with high-to-moderate node density in which the opportunity that the moving nodes can meet with each other is rather high. On the other hand, the delivery ratio becomes remarkably low in the sparse network environment especially when there is a strict constraint on message delivery deadline. In this paper, we introduce the novel concept of rendezvous place where the passing nodes can announce, deposit, or pick up their own messages without having to meet the other nodes carrying the desired message. The rendezvous place can be detected automatically and its area's shape is dynamically changed according to the interaction among nodes. The results from extensive simulations show that our routing algorithm can achieve higher delivery ratio and utilize lower energy consumption than traditional opportunistic routing algorithms especially in sparse network environment.